Pengaruh Beban Kerja terhadap Kinerja Karyawan Unit Airport Operation Landside & Terminal di Bandar Udara Internasional Yogyakarta - Putra, Alfa Alvian Andika (Al-DYAS, 2024)
This research was conducted at the Airport Operation Landside & Terminal (AOLT) Unit at Yogyakarta International Airport. The purpose of this study was to determine the effect between workload on employee performance and to find how much influence between the independent variable, namely workload, on the dependent variable, namely performance. This research uses quantitative research methods with data collection techniques using questionnaires distributed to employees of the Airport Operation Landside & Terminal unit. The T test results show that workload has a significance value of 0.151 on performance. Then, the coefficient of determination test shows that workload has 50.7% influence on performance.